2006 IEEE Computer Society Conference on Computer Vision and Pattern Recognition - Volume 2 (CVPR'06)
DOI: 10.1109/cvpr.2006.225
|View full text |Cite
|
Sign up to set email alerts
|

Piecewise Image Registration in the Presence of Multiple Large Motions

Abstract: a) Left image (b) Right image (c) Labeled flow field (d) Reconstructed image Figure 1. Dense pixel correspondence between two images of a scene with moving rigid objects. Images (a) and (b) are the input, and (c) is the flow field from (a) to (b) with color labelings. Red indicates occluded areas, and blue and green indicate two motions modeled by fundamental matrices for the bird and the rest of the background(note that the flow vectors are uniformly scaled to a shorter length for visual clarity). Image (d) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…of points to be matched is below some threshold. The above process is similar to the work of [13] and [14]. Different from them, before implementing RANSAC, we remove mismatches by our previous proposed method [15].…”
Section: Motion Discoverymentioning
confidence: 99%
“…of points to be matched is below some threshold. The above process is similar to the work of [13] and [14]. Different from them, before implementing RANSAC, we remove mismatches by our previous proposed method [15].…”
Section: Motion Discoverymentioning
confidence: 99%
“…Image de-noising was one of the first Graph Cuts applications, and it has recently been shown that Graph Cuts can be used for image registration [15,16,17,18,19,20,21]. We propose a joint approach, where image de-noising helps the registration process, and the good overlap of a clearer image improves de-noising of a corrupted image.…”
Section: Introductionmentioning
confidence: 99%
“…The Photomontage and related work [1,3] are most related to our work, in that they also use a stack of similar images to create a new composite image. However, the main goal of [1] is to create a composition that is visually better than any of the original ones and it has a lot of manual intervention (it is mainly an artist's tool).…”
Section: Introductionmentioning
confidence: 99%
“…However, the main goal of [1] is to create a composition that is visually better than any of the original ones and it has a lot of manual intervention (it is mainly an artist's tool). [3] uses only one reference image and assumes that the location of input paired images is known. One of our baseline algorithms is an adapted version of [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation